Growth and Yield Performance of Aromatic Fine Rice as Influenced by Varieties and Fertilizer Managements - Shams Islam; Md. Al Mamun Or Roshid; Md. Shafiqul Islam Sikdar; Md. Sohrab Hossain (Green Engineering Society, 2021)
This Research was conducted to investigate the effect of fertilizer management on growth and yield performance of aromatic fine rice varieties. The experiment consisted of two factors were aromatic fine rice and fertilizer management. There were four varieties namely Kalizira, Kataribhog, Tulshimala and BRRI Dhan34 with four fertilizer treatments recommended dose of fertilizers (T1), cowdung @ 10 tha-1 (T2), 50% of recommended dose of fertilizers + 50% cowdung(T3), 75% of recommended dose of fertilizers + 50% cowdung (T4). The result showed that BRRI Dhan 34 significantly superior for effective tillers number/ hill (18.46), panicles length (26.67cm), grains number/ panicle (146.30), harvest index (40.73 %), grain protein content (6.23%), grain yield (2.79 tha-1), straw yield (4.06 tha-1), and biological yield (6.85 tha-1). Among fertilizer management, the highest effective tillers number/hill (16.20), grains number/ panicle (142.45, panicles length (26.66 cm),1000 grain weight (13.75), grain protein content (10.2%), biological yield (6.30), were obtained from T3 treatment. Based on interaction effect showed that the highest effective tillers number/hill (18.36), grains number/ panicle (155.33), panicles length (26.73 cm), grain protein content (10.80%), biological yield (7.85) was found with BRRI Dhan 34 combined with T3 treatment. However, grain yield increased with the increase in nitrogen levels. Together tillers number/hill, grains number/panicle, grain protein content, harvest index, grain yield was the main responsible yield contributing characters to improve the yield quality of aromatic fine rice.